2009
DOI: 10.1021/jp9050947
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles and Thin Film Formation in Ultrashort Pulsed Laser Deposition of Vanadium Oxide

Abstract: The ultrashort pulsed laser deposition of vanadium oxide thin films has been carried out by a frequency-doubled Nd:glass laser with a pulse duration of 250 fs. The characteristics of the plasma produced by the laser−target interaction have been studied by ICCD imaging and optical emission spectroscopy. The results confirm that an emitting plasma produced by ultrashort laser pulses is formed by both a primary and a secondary component. The secondary component consists of particles with a nanometric size, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 37 publications
2
25
0
Order By: Relevance
“…In the ultra-short ablation of a large number of systems, as it is reported in literature [6][7][8]12,25], the presence of two different laser induced emissions can be distinguished: a first plasma (primary plume) lasting for few hundreds of nanosecond and characterized by the presence of electronic transitions of atomic and ionic emissions and a second one (secondary component or plume) starting after few microseconds and showing a typical black-body like emission spectrum. The emission produced by ultra-short laser ablation of the ZrB 12 target presents a particular characteristic, in fact, together with the primary and secondary plumes also a third emission of material is present.…”
Section: Plasma Analysismentioning
confidence: 85%
See 2 more Smart Citations
“…In the ultra-short ablation of a large number of systems, as it is reported in literature [6][7][8]12,25], the presence of two different laser induced emissions can be distinguished: a first plasma (primary plume) lasting for few hundreds of nanosecond and characterized by the presence of electronic transitions of atomic and ionic emissions and a second one (secondary component or plume) starting after few microseconds and showing a typical black-body like emission spectrum. The emission produced by ultra-short laser ablation of the ZrB 12 target presents a particular characteristic, in fact, together with the primary and secondary plumes also a third emission of material is present.…”
Section: Plasma Analysismentioning
confidence: 85%
“…Usually, thin films obtained by ultra-short PLD are formed by particles ranging from tens to hundreds of nanometers in diameter and no larger particles are present onto their surfaces [6][7][8]. Fig.…”
Section: Target and Films Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the existence of the (220)-oriented peak, which is beneficial for reducing the surface recombination of the CIGS absorber layer due to higher work function, is largely preserved only in films grown by the fs-PLD [13]. Preliminary studies have also shown that the relaxed structure usually accompanies with the broadened peak of (112) orientation, which is associated with high degree of structural disorder [14]. The high degree of structural disorder can be successfully suppressed for the fs-PLD CIGS thin film because of the well-crystalline characteristics confirmed by XRD spectra.…”
Section: Resultsmentioning
confidence: 99%
“…In the previous decades, the fabrication of V 2 O 3 was mainly focused on bulk powders and spherical particles [23,[27][28][29][30][31][32]. Recently, some techniques for preparing V 2 O 3 with a novel morphology have been reported.…”
Section: Introductionmentioning
confidence: 99%